PENGARUH KOMPRES HANGAT UNTUK MENURUNKAN SUHU TUBUH ANAK YANG MENDERITA DEMAM DENGAN MASALAH UTAMA HIPERTERMI - Andes Maslikhatul M; P. Sulistyowati; Rahaju Ningtyas (Jurnal Ilmiah Medsains, 2023)
Childhood is the golden age of education and human resources for physical growth and intelligence and must be supported by good nutrition and a healthy environment. Fever is a sign of a disease that attacks the body's immune system, handling fever in children can be done with warm compresses, giving fluids, adequate rest and giving antipyretics if necessary. this study was to determine the impact of warm compresses on reducing fever in children with fever. This type of qualitative research with a case study approach is used in this paper. information disaggregation method to obtain appropriate and appropriate information for the study of this situation, the creators involved the information disaggregation procedure as encounter and perception. Inclusion criteria were pediatric patients aged 5-12 years with a temperature >37.5ÂºC and exclusion criteria were pediatric patients aged >12 years and temperatures <37.5ÂºC with impaired skin integrity. the results of the implementation of nursing state that the warm compress technique has less effect or impact on the child having a fever due to a long infection. the effect of warm compresses on reducing the body temperature of children with fever is less influential because there are accompanying inhibiting factors.